0285 Sex As A Biological Variable On The Inflammatory Effects Of Intermittent Hypoxia. (12th April 2019) - Armond, Richard De; Morton, Christopher; Patel, Salma I; Combs, Daniel; Parthasarathy, Sairam
Abstract: Introduction: Intermittent hypoxia (IH) occurs in patients with obstructive sleep apnea (OSA), which, in turn, has been associated with cardiovascular mortality. However, in observational studies, the adverse events are more pronounced in men compared to women. The mechanisms underlying such sex differences are unknown, but inflammation has been posited as a mechanism by which OSA causes cardiac disease. We aimed to determine sex differences in pro-inflammatory cytokine production by peripheral blood mononuclear cells (PBMCs) in response to in-vitro IH. We hypothesized that PBMCs derived from men produce more interleukin-6 when stimulated in-vitro with IH than PBMCs derived from women. Methods: After overnight sleep study, venipuncture was performed and PBMCs isolated and then resuspended into specialized cell culture cassettes that allowed for oxygen and nitrogen permeability. Cells were divided into two culture preparations - one subjected to normoxia (in the incubator) and the other to IH in a programmable hypoxia chamber (Oxycycler C-chambers; Biospherix, Inc.). The IH consisted of 5 cycles/ hour with a baseline of 20.9% and nadir of 5% FiO2 . After 18 hours of incubation, the supernatant was collected and Interleukin-6 was measured using ELISA techniques (R&D Systems). Results: In 39 individuals (19 men) who had OSA (n=14), asthma (n=8), chronic obstructive pulmonary disease (n=3) or healthy (n=14) confounding factors that could influence production of IL-6 by PBMCs were obtained: age, body mass index, anti-inflammatory medications, smoking history, serum testosterone levels, and number of cells in culture. PBMCs from men produced greater levels of IL-6 following exposure to IH when compared to PBMCs in normoxic conditions. In contrast, PBMCs from women appeared to produce less IL-6 following exposure to IH than those cells exposed to normoxia. These differences were adjusted for confounders and there remained an interactive effect between IH and sex (F=4.68; P=0.038); anti-inflammatory medications (F=11.4; P=0.002) and a tendency for plasma testosterone levels (F=2.7; P=0.11). Conclusion: Sex differences in cellular response to intermittent hypoxia may explain epidemiological observations of sex as a biological variable in studies involving OSA and cardiovascular mortality. Support (If Any): Unfunded